Values as the Basis of Meaningfulness of Life - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2005)
The importance of meaning in human's life is raised in the article. According to the philosophical and psychological literature, meaning is defined as a basis human life. Herewith, a problem of discovery of meaning in a contemporary society is defined, in which a lot of people experience the feeling of inanity or lose their identity and human dignity. The beginning of these negative phenomena are associated with nowadays individual's alienation from spiritual values, which help to orientate in the world and find what is meaningful in it. There is an attempt to define the spiritual values, which form the basis of the meaning of life. According to systematic and hierarchical codes, the priority is given to the moral values as the core of the good, which has a close connection with the truth, the beauty and sanctity. There is also the attitude of elder pupil's towards the search of purport and their connection with spiritual values revealed in this article.
Keywords: values; spirituality; moral education; identity; meaningfulness